Targeting the Cysteine Redox Proteome in Parkinson's Disease: The Role of Glutathione Precursors and Beyond - Marcos A. Martinez-Banaclocha (MDPI AG, 2023)
Encouraging recent data on the molecular pathways underlying aging have identified variants and expansions of genes associated with DNA replication and repair, telomere and stem cell maintenance, regulation of the redox microenvironment, and intercellular communication. In addition, cell rejuvenation requires silencing some transcription factors and the activation of pluripotency, indicating that hidden molecular networks must integrate and synchronize all these cellular mechanisms. Therefore, in addition to gene sequence expansions and variations associated with senescence, the optimization of transcriptional regulation and protein crosstalk is essential. The protein cysteinome is crucial in cellular regulation and plays unexpected roles in the aging of complex organisms, which show cumulative somatic mutations, telomere attrition, epigenetic modifications, and oxidative dysregulation, culminating in cellular senescence. The cysteine thiol groups are highly redox-active, allowing high functional versatility as structural disulfides, redox-active disulfides, active-site nucleophiles, proton donors, and metal ligands to participate in multiple regulatory sites in proteins. Also, antioxidant systems control diverse cellular functions, including the transcription machinery, which partially depends on the catalytically active cysteines that can reduce disulfide bonds in numerous target proteins, driving their biological integration. Since we have previously proposed a fundamental role of cysteine-mediated redox deregulation in neurodegeneration, we suggest that cellular rejuvenation of the cysteine redox proteome using GSH precursors, like N-acetyl-cysteine, is an underestimated multitarget therapeutic approach that would be particularly beneficial in Parkinson's disease.